A methods engineering study on Meralco Corporate Meter Division - Cinco, Ronald Allan M. (College of Engineering, 2000)
The Corporate Meter Division of Manila Electric Company (MERALCO) ensures the customers that the meters they receive are 100 percent accurate and are always in good condition. It is in charge of the repair, recondition, and calibration of electric meters. It is operating in the MERALCO Compound at Ortigas Avenue, Pasig City. The group gathered relative information about the company's operations. A time study has been conducted on the calibration of Single-Phase electric meters in the QUALYTEST machine. It has been determined that the standard time is STp= 80:20.09 min/20 meters. The group observed that even though the processes in the plant is going well, there are still areas where difficulty is encountered especially in the areas of layout - lack of space and blocked pathways, materials handling and storage - lack of space in the storage area, systems and procedures - delays in updating meter status, assignment of tasks - function of technicians and worktables are not permanent. Upon proper analysis of the above stated problems, the group has arrived with several alternatives. The following are the chosen alternatives : plant layout- work improvement team's (WIT) proposed layout, materials handling and storage - new mobile meter storage racks, permanent storage racks- these would ease the accessing of the boxes of meters particularly to the ones placed on the bottom, proper disposal of junk meters- the space occupying the junk meters can be utilized for other meters. Bar coding scheme for the inventory of meters - this would improve the speed and the accuracy of the operation immensely. Systems and procedures - phasing out of old forms, encourage ordering of meters in the Materials Management Systems (MMS), Strict implementation of policies, For idle workers, assign them to help other technicians.